El papel de la Unión Europea y de los Estados Unidos en el desarrollo rural integral en Colombia en los gobiernos Pastrana y Uribe (2017)
"This article shows a comparative exercise between the cooperation strategies that have affected the Colombian rural sector since the year 1999 to the present imparted by the European Union and the United States. We evaluate the changes, advances and criticisms that the implementation of these programs have had in recent governments between 1999 and 2012. We have found, from the difference of the EU and US strategy, that the cooperation agenda has varied in the last Governments and have influenced the way in which the rural sector has been developed". -- Tomado del Formato de Documento de Grado.